Ritual Communication of â€œMassawa Traditionâ€ in Turu Cinnae Village, Lamuru District, Bone Regency - Azdar, Afriyanti; Fatimah, Fatimah; Maesurah, Sitti (Palakka : Media and Islamic Communication, 2024)
This study discusses the communication of the massawa tradition ritual in Turu Cinnae Village, Lamuru District, Bone Regency, which aims to analyze the public perception of the massawa tradition in Turu Cinnae Village, Lamuru District, Bone Regency and to find out the communication process of the massawa tradition ritual in Turu Cinnae Village, Lamuru District, Bone Regency. This study uses a qualitative descriptive research type with a communication science and sociology approach. The results of this study indicate that, first,The Massawa tradition was carried out starting from the community's anxiety when hit by the dry season so that the traditional elders took the initiative to find a way for rain to fall immediately and the community could resume their agricultural activities. Massawa is carried out as a sign of gratitude for the agricultural products obtained each year, and the purpose of carrying out the Massawa tradition is to ward off disasters and passappo wanua which is carried out before returning to farming on agricultural land. Second,The ritual communication of the massawa tradition carried out in Turu Cinnae Village, Lamuru District, Bone Regency begins with the stages of tudang sipulung, mattanra esso, and matteppang paddumpu. The process of ritual communication of the massawa tradition is divided into three places, namely in the bola battoa, the sanro wanua house, and the residents' houses. In the ritual process, there are several tools and equipment that contain meaning such as incense, frankincense, bananas, betel leaves, rice, young coconut, eggs, and water.